Pharmacokinetic drug interactions of asciminib with the sensitive cytochrome P450 probe substrates midazolam, warfarin, and repaglinide in healthy participants. Issue 6 (15th March 2022) - Hoch, Matthias; Sengupta, Tirtha; Hourcade‐Potelleret, Florence
Abstract: Asciminib, a first‐in‐class BCR‐ABL1 inhibitor that works by Specifically Targeting the ABL Myristoyl Pocket (STAMP), is a new treatment option for patients with chronic myeloid leukemia who no longer benefit from currently approved tyrosine kinase inhibitors. In vitro, asciminib reversibly inhibits cytochrome P450 (CYP) 3A4/5, CYP2C9, and CYP2C8. This phase I, open‐label, two‐stage study in healthy participants evaluated the effect of asciminib (40 mg b.i.d. at steady‐state) as a potential perpetrator on single‐dose pharmacokinetics of a two‐drug cocktail containing midazolam (CYP3A substrate) and warfarin (CYP2C9 substrate) in stage 1 ( n  = 22), and of repaglinide (CYP2C8 substrate) in stage 2 ( n  = 25). For midazolam plus asciminib versus midazolam, geometric mean ( G mean ) ratios (90% confidence interval) for midazolam area under the curve from zero to infinity (AUCinf ) and maximum plasma concentration (Cmax ) were 1.28 (1.15, 1.43) and 1.11 (0.96, 1.28), respectively. For warfarin plus asciminib versus warfarin, G mean ratios for S‐warfarin AUCinf and Cmax were 1.41 (1.37, 1.45) and 1.08 (1.04, 1.13), respectively. Results for R‐warfarin were in line with those for S‐warfarin. For repaglinide plus asciminib versus repaglinide, G mean ratios for AUCinf and Cmax were 1.08 (1.02, 1.14) and 1.14 (1.01, 1.28), respectively. The treatments were generally well tolerated, and the asciminib safety profile was consistent with previous studies of asciminib in the absence of probe substrates. Overall, the results indicate that asciminib (40 mg b.i.d.) is a weak inhibitor of CYP3A and CYP2C9 and has no meaningful effect on CYP2C8.